2018
DOI: 10.1371/journal.pone.0199939
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Huanjiang mini-pigs exhibit differences in nutrient composition according to body weight and gestational period

Abstract: Low birth weight may negatively affect energy storage and nutrient metabolism, and impair fetal growth and development. We analyzed effects of body weight (BW) and gestational period on nutrient composition in fetal Huanjiang mini-pigs. Fetuses with the lowest BW (LBW), middle BW (MBW), and highest BW (HBW) were collected at days 45, 75, and 110 of gestation. Crude protein (CP), crude fat, amino acid (AA), and fatty acid (FA) concentrations were determined. The BW gain, carcass weight, fat percentage, and uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…We also found that the dominant phyla in jejunal and ileal contents was Firmicutes, and those in colonic contents were Firmicutes, Bacteroidetes, and Actinobacteria, which is consistence with previous studies [15,13]. In addition, lower Firmicutes abundance and Firmicutes/Bacteroidetes ratio were observed in the ileum from days 45 to 110 of gestation, which is in line with the changes of body fat percentage of sows [11]. However, earlier studies showed that obesity were associated with increased Firmicutes abundance and Firmicutes/Bacteroidetes ratio [20,21].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We also found that the dominant phyla in jejunal and ileal contents was Firmicutes, and those in colonic contents were Firmicutes, Bacteroidetes, and Actinobacteria, which is consistence with previous studies [15,13]. In addition, lower Firmicutes abundance and Firmicutes/Bacteroidetes ratio were observed in the ileum from days 45 to 110 of gestation, which is in line with the changes of body fat percentage of sows [11]. However, earlier studies showed that obesity were associated with increased Firmicutes abundance and Firmicutes/Bacteroidetes ratio [20,21].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the abundance of Lactobacillus reduced in jejunum and ileum ongoing with pregnancy. Consistence with the changes of Lactobacillus abundance, the sows are more obese at the late pregnancy [11], indicating that Lactobacillus was associated with changed maternal metabolism during the pregnancy. Obese women had higher number of mutants Streptococcus compared to normal-weight women [26], and higher Streptococcus colonization was also signi cantly associated with obesity in children [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IUGR usually lead to alteration of the postnatal growth, together with anomalies related to glucose, cholesterol, and triglyceride metabolism ( 6 , 7 ). When Huanjiang mini-pigs are fed with diets containing lower nutrient level or with imbalanced diets they display lower BW at first service and bigger litter size, thus explaining why Huanjiang mini-pigs are much susceptible to low birth weight ( 8 ).…”
Section: Introductionmentioning
confidence: 99%